Analysis of rational prescribing in “X” Hospital, Jakarta - Nurul Habibah; Lilian Batubara (Bagian Farmakologi, Fakultas Kedokteran Universitas YARSI, 2020)
Background: The irrational prescribing is one of the problems in health care in Indonesia. The irrational prescribing can cause medication errors, increase costs, the possibility of adverse drug side effects or drug interactions that may inhibit the quality of care. The purpose of this study is to know the rationality of drug prescribing in March 2016 in Hospital X, Jakarta.Methods: This study assessed a prescribing which admitted in March at X hospital with descriptive analysis design and samples taken by multistage sampling.Results: 384 prescription were used and the results of this study : 23,96 % (92) rational prescribing, 5,47 % (21) incomplete administrative prescription, 15.88% (61) overprescribing, 11.20% (43) underprescribing, 15,36 % (59) multiple prescribing, 4.95 % (19) extravagant prescribing and 23.18% (89) polypharmacy.Conclusion: Rational presription 23.96% and the most irrational prescription form is polypharmacy 23.18% .